Strategy Models in Learning of Islamic Education in Essensialism Philosophy Perspective - Fahruddin A Rahman (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2017)
This research discusses how models of learning strategies of Islamic religious education; second, how the learning concept of essentialism philosophy; third, how the models of learning strategy of Islamic education in essentialism philosophy perpesktif.The type of research in this thesis uses library research, with a qualitative approach; data collection method: documentary method, that is to collect data and information on library materials relevant to research object; is data analysis with deductive method and inductive method.The research findings in this thesis can be summarized: First: The learning strategy of Islamic Education is a conceptual framework that serves as a guide for education designers and implementers. Learning strategy models used are student-centered learning strategies such as, co-operative, contextual and Active; Second: The essentialism philosophy is an educational philosophy that argues that education must have a firm footing of old cultural values, historical legacies, which have been proven to bring goodness to life. The models of instructional strategies in the essentialism philosophy  perspective are teacher-centered learning strategies (Teacher Centered); Third: The use of learning strategy models that emphasize student activities, students as subjects (Student Centered), such as contextual learning (CTL), Active learning, and Cooperative learning, should not reduce and completely eliminate the existence of teachers. However, the success of education or learning in educating, teaching, and shaping student characteristics lies in the extent of teacher role involvement in education and learning itself. Keywords: Learning Strategy, Essentialism Philosophy, Models